Efisiensi Pemasaran Bunga Potong Krisan di Kabupaten Cianjur - Wisnu Ardi Pratama; Rita Nurmalina; Nia Rosiana (Jurnal Ilmu Pertanian Indonesia, 2023)
Chrysanthemum cur flowers have many benefits in that they can be used for flower bouquets, pollution absorbers, and even traditional medicinal plants. One of the national chrysanthemum cutting flower centers is in Cianjur Regency, which contributes 53% of total production for West Java Province. Every year, this high production of cut flowers is also followed by higher price differences between the farmer and final seller levels. This study aims to analyze the efficiency of chrysanthemum cut flower marketing in Cianjur Regency. Respondents included farmers, collectors, wholesalers, and florists. Marketing efficiency was analyzed using the composite index method and the Acharya & Aggarwal method, using three indicators: marketing margin, farmer's share, and marketing costs. There are three marketing channels in Cianjur Regency, namely (1) farmers–collectors–wholesalers–consumers, (2) farmers– wholesalers–consumers, and (3) farmers–florists–consumers. The most efficient marketing channel is channel 2, with the lowest index, 1, and based on the Acharya & Aggarwal method, channel 2 has the highest efficiency value, 1.14. Therefore, it can be concluded that farmers' most preferred marketing channel is channel 1 (collectors), which is not the most efficient channel. Preferably, the farmers choose channel 2 (wholesalers) to sell the harvest of their chrysanthemum cut flowers so as not to rely on collectors. Keywords: farmer's Saham, marketing channel, marketing margin